Application and Optimization of Natural Language Processing Technology in Intelligent Customer Service System - Qi, Shuai (Journal of Theory and Practice of Management Science, 2025)
In today's global digital transformation wave, it is increasingly urgent for enterprises to pursue efficient and accurate customer service. With the expansion of business scale and the diversification of customer needs, traditional customer service models have gradually exposed problems such as slow response speed, low processing efficiency, and uneven service quality, which are difficult to meet the customer service needs of modern enterprises. In this context, the introduction of natural language processing technology has injected new vitality into the development of intelligent customer service systems. NLP technology simulates human language processing ability through advanced technologies such as deep learning and machine learning, enabling computers to accurately understand and generate natural language, greatly improving the interaction ability and service efficiency of intelligent customer service systems. The introduction of this technology not only provides more convenient and efficient customer service solutions for enterprises, but also provides strong support for their digital transformation and intelligent upgrading.